PERAN REPRODUKTIF DAN PRODUKTIF IBU PENJUAL SAYUR (Studi tentang Kehidupan, Pola Pembagian Kerja dan Beban Kerja yang dialami Ibu Penjual Sayur di Pasar Pedurungan, Kecamatan Pedurungan Kota Semarang) - Setia Iriyanto; Eny Winaryati (JURNAL LITBANG, 2006)
ABSTRACT The purpose of this research is to get the information about the contribution of the women tkat selling vegetables in Pedurungan traditional market, that have functions in the term of reproductivity, that related with the productive function, and the productivity that related with the productive function, such as their contribution in the process in making a living and all the consequence that should be foced by them, as a mother, a housewife and a citizen for 24 hours, and what is the effects of it to their income and the controlling to their income qnd about sharing ability within their husband or the other family's member. The population in this research are all the women that have age between 15 - 46 years old, in Pedurungan traditional market, Kecamatan Pedurungan, Semarang, and the sample's population are 39 women. We can conclude from this research that almost all the women were very young when they were getting married and in having a baby. The rate of pregnancy were 3 times or more in the term of controlling their pregnancy, birth and their awareness in using the contraception tools was in a good rate. The productivity function of these women about the working hour were more than l2 hours per day, and the sharing ability within their husband in making a living is still low, The expectation from this research is the development of awareness of the society and all the husband about the women's rights and needs, that related with economic welfare, good sanitation and respectivity. Keywords : Reproductive and women